2013
DOI: 10.1063/1.4819018
|View full text |Cite
|
Sign up to set email alerts
|

On the beneficial role of noise in resistive switching

Abstract: We study the effect of external noise on resistive switching. Experimental results on a manganite sample are presented showing that there is an optimal noise amplitude that maximizes the contrast between high and low resistive states. By means of numerical simulations, we study the causes underlying the observed behavior. We find that experimental results can be related to general characteristics of the equations governing the system dynamics.Comment: 4 pages, 5 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 18 publications
1
20
0
2
Order By: Relevance
“…[8,9], we conducted a large number of simulations to understand the observed behavior. The model employed is presented in the next section.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[8,9], we conducted a large number of simulations to understand the observed behavior. The model employed is presented in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…[8,9]. It was shown that any symmetric perturbation in the input current i(t) will increase the mean velocity from Eq.…”
Section: R B I(t) R(xi)mentioning
confidence: 96%
See 2 more Smart Citations
“…Several reports [47,48] have already shown the importance of noise in the response of memristive devices to the external driving field. However, the approach used is limited to the case of a bistable system and must be extended to the multi-stable energetic profile describing the real situation more correctly.…”
Section: Noise-induced Phenomenamentioning
confidence: 99%